Daya Hambat Air Kelapa (Cocos nucifera) terhadap Pertumbuhan Bakteri Salmonella typhi dan Escherichia coli - Fera Sartika (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Coconut products are known to have anti-bacterial activity. One product of coconut is coconut water. Coconut water has benefits in food processing, especially for health. Coconut water contains tannin or antidote (anti-poison) which is antibacterial which will inhibit bacterial growth. This study aims to determine the antimicrobial effects of coconut water by testing the inhibition of Salmonella typhi and Escherichia coli bacteria. This type of research uses experimental or experimental methods. Before the inhibitory test is carried out, phytochemical tests of coconut water are carried out such as flavonoids, alkaloids, tannins, saponins, and steroids. The results showed that coconut water does not contain the chemical compounds of flavonoids, alkaloids, tannins, saponins, and steroids. The results of the inhibitory test indicate that coconut water cannot inhibit the growth of Salmonella typhi and Escherichia coli bacteria.